2010
DOI: 10.1007/s12011-010-8850-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Ligands on Accumulation of Copper in Hyperaccumulator and Nonaccumulator Commelina communis

Abstract: Better understanding of copper uptake and accumulation regulation in plants is critical to the phytoremediation of copper contaminated soil. This study employed a 30-day pot experiment to assess the relationship between organic ligands and copper accumulation in plants. Hyperaccumulator and nonaccumulator varieties of Commelina communis were used, different organic ligands were applied, and the data of copper accumulation in shoots were collected. The six organic ligands included ethylenediaminetetraacetic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In general, organic acids can bind trace metal ions in soil solution by complexation reactions, making them more available for plant uptake (Wang and Zhong, 2011). However, organic acids can also reduce the soil pH and solubilize some non-labile fraction of trace metals in soil, thus enhancing trace metal availability (Perez-Esteban et al, 2013).…”
Section: Root Chelation and Compartmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, organic acids can bind trace metal ions in soil solution by complexation reactions, making them more available for plant uptake (Wang and Zhong, 2011). However, organic acids can also reduce the soil pH and solubilize some non-labile fraction of trace metals in soil, thus enhancing trace metal availability (Perez-Esteban et al, 2013).…”
Section: Root Chelation and Compartmentationmentioning
confidence: 99%
“…Some trace metals are chelated by organic acids, which are involved in trace metal absorption by plant roots, translocation in the xylem, and storage in the vacuole of leaf cells (Larbi et al, 2010;Wang and Zhong, 2011). Trace metals can also be bound by nicotianamine (NA) and mobilized by the yellow strike-like (YSL) family transporters (Chu et al, 2010;Harris et al, 2012).…”
Section: Translocationmentioning
confidence: 99%
“…In soil, the predominant input of them is from root exudates, dead plant material and microbial decomposition products. Organic manures can also contain large amounts of organic acids (Wang and Zhong 2011). These root exudates are implicated in the weathering of soil minerals, mobilisation of soil nutrients (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They are able to form complexes with metal ions and modify the mobility of the metals in the rhizosphere (Maturi and Reddy 2008;Renella et al 2004) and their exudation is probably an internal mechanism against toxic effects of trace elements (Gasecka et al 2012). However, there is little information in the literature concerning the mechanism of how these compounds affect trace element accumulation in plants (Wang and Zhong 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic plant communities are good candidates for treating groundwater contamination in engineered systems because of the large surface area, ease of culture and high organic uptake potential 15 . The Co and Cu accumulators have been found in more than dozen families [16][17][18][19][20][21][22] . Based on the database, Akhani et al have recently demonstrated that the flora of the south Caspian Area included 3234 species belonging to 856 genera and 148 families of vascular plants which are known from the geographic boundaries of the three provinces Gilan, Mazandaran and Golestan and Talish in Azerbaijan Republic.…”
mentioning
confidence: 99%